Prognostic impact of immunophenotypic aberrancies of blasts in lower risk myelodysplastic syndrome. (2022) - Corrao, Kristen; Rezwan, Siam; Atallah, Ehab; Michaelis, Laura C; Runaas, Lyndsey; Harrington, Alexandra M.; Abedin, Sameem
Abstract: Objective/background: Low risk myelodysplastic syndrome (MDS) is a marrow failure state eventually leading to transfusion dependence. Flow cytometry has previously been demonstrated as prognostic tool in MDS, however not thoroughly studied in lower risk MDS. In this study, we assessed whether assessment for immunophenotypic blast aberrancies by flow in low risk MDS patients has a prognostic role in these patients. Methods: A total of 63 consecutive patients diagnosed with low/intermediate risk MDS were included. We recorded initial flow results, and collected time to transfusion dependence, and AML progression. Results: On multivariate cox regression analysis, increasing IPSS-R score, an increase in the number of blast aberrancies on flow cytometry, and aberrant expression of CD7 on myeloid blasts increased likelihood of transfusion dependence. Conclusion:Low risk MDS patients with increasingly aberrant blast phenotypes by flow may be at risk for earlier transfusion dependence.